2015
DOI: 10.1186/s12885-015-1229-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting connexin 43 with α–connexin carboxyl-terminal (ACT1) peptide enhances the activity of the targeted inhibitors, tamoxifen and lapatinib, in breast cancer: clinical implication for ACT1

Abstract: BackgroundTreatment failure is a critical issue in breast cancer and identifying useful interventions that optimize current cancer therapies remains a critical unmet need. Expression and functional studies have identified connexins (Cxs), a family of gap junction proteins, as potential tumor suppressors. Studies suggest that Cx43 has a role in breast cancer cell proliferation, differentiation, and migration. Although pan-gap junction drugs are available, the lack of specificity of these agents increases the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 58 publications
3
58
0
Order By: Relevance
“…For instance, a peptide (αCT1) mimicking the C-terminal of Cx43, blocking ZO1 interacting with Cx43, was shown to cause specific inhibition of Cx43 hemichannel function (but maintaining GJIC), which prevented temozolomide resistance in human glioblastoma cell lines 237 . In another study the same peptide augmented the effect of the oestrogen receptor modulator tamoxifen and the ERBB2 inhibitor lapatinib in breast cancer cell lines, although the authors suggested the key function of the peptide in this setting was to enhance GJIC 238 . The exact mode of action of this peptide appears complex and perhaps even context-dependent.…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…For instance, a peptide (αCT1) mimicking the C-terminal of Cx43, blocking ZO1 interacting with Cx43, was shown to cause specific inhibition of Cx43 hemichannel function (but maintaining GJIC), which prevented temozolomide resistance in human glioblastoma cell lines 237 . In another study the same peptide augmented the effect of the oestrogen receptor modulator tamoxifen and the ERBB2 inhibitor lapatinib in breast cancer cell lines, although the authors suggested the key function of the peptide in this setting was to enhance GJIC 238 . The exact mode of action of this peptide appears complex and perhaps even context-dependent.…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…Later, more specific approaches have been developed including siRNA and short peptides with specific sequences homologous to intracellular and extracellular connexin domains, termed connexin mimetic peptides (Iyyathurai et al, 2013). ACT1 peptide targeting a portion of Cx43 C-terminus enhances GJIC for potential therapies in wound healing and cancer (Grek et al, 2015a; Grek et al, 2015b). Given that connexin hemichannels operate independently of gap junctions and also serve different roles in cell physiology and pathology, several peptides that target to extracellular loop regions of Cx43 have been developed and some of them exhibit stronger inhibitory effects against hemichannels than GJIC.…”
Section: Current Therapeutic Strategies Targeting Connexins Gap Jmentioning
confidence: 99%
“…Cx43 expression was associated with increased malignancy in multiple cancers [26][27][28]. Especially, a previous study reported that miR-206 inhibited the migration and invasion of breast cancer by targeting at Cx43 [25].…”
Section: Discussionmentioning
confidence: 99%